America's First Great Depression : Economic Crisis and Political Disorder after the Panic of 1837 - Roberts, Alasdair (Alasdair Scott) (Book collections on Project MUSE., 2012)
This title is a history of American financial policy in the 1830's and 1840's. Alasdair Roberts's contention that international financial considerations shaped US policy making is well sustained and the argument is documented with a wealth of evidence.